Risk Management, Governance and Financing Issues in Public-Private Partnerships Transportation Projects - Mandiartha, Putu; Intan Suhana, Mohd Razelan; Azlina, Ismail (Universiti Malaysia Pahang, 2017)
This paper discusses issues related to risk management, governance, and financing of public-private partnerships transportation projects. The allocation of risks and the requirements for ownership and equity provision are examined through analysis of a range of contracts. Lesson learn from a series of Australia’s public-private partnerships transportation projects are also presented. The results show that from the perspective of risk allocation, the arrangements are consistent among the projects. Some fluctuations, however, are observed in term of equity provision. Initially, the contracts are developed based on the private sector taking full traffic demand risk and promising outcomes led to revenue sharing clauses being introduced, later overoptimistic demand forecasts resulted in the market rejecting acceptance of traffic demand risk. The paper also presents the variation between the case study projects in terms of excess revenue sharing. The analysis also suggests that, in arranging these types of projects, traffic demand issue is prominent and should be given major concern since it is closely related with the revenue of the projects which in turns affect the equity of the projects.